Traversing the Interconnected Dynamics of Climate Change And Food Security in Sub-Saharan Africa - Nana Yaw Brenya AGYEMAN; Benjamin DAMOAH; Elijah Osei Manu (PT Keberlanjutan Strategis Indonesia, 2025)
Globally, Climate change adversely impacts people's lives. Climate change has not spared Sub-Saharan Africa in terms of farming and food security. Sub-Saharan Africa's overdependence on agriculture and farming adversely impacts the standard of living and quality of life. This study explored secondary data analysis of global institutions' reports to examine the impact of climate change on food security in Sub-Saharan Africa. The paper synthesizes themes and patterns to comprehend the effects of climate change on food supply. The data was analyzed through a thematic analysis to identify patterns and themes from the secondary data. The findings established that climate change reduces farming productivity, which causes food shortages and increases the vulnerability of farming. Food security can be improved by adopting climate-change agricultural practices and increasing investment in agricultural infrastructure. The paper concludes that climate change impacts food security. This paper recommends that the government and global institutions support Sub-Saharan African farmers. It contributes to raising awareness of measures to improve food security in Sub-Saharan Africa.